(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article deals with the principles of electronic document management systems, comparison of various EDS presented on the Russian market of automated information systems. The article analyzes the history of implementation of the "DELO" SED in the activities of state and commercial organizations, highlights the prospects for the development of this system in a highly competitive environment.